Proceedings of the 14th International Conference on World Wide Web - WWW '05 2005
DOI: 10.1145/1060745.1060799
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility

Abstract: Currently, the vast majority of web sites do not support accessibility for visually impaired users. Usually, these users have to rely on screen readers: applications that sequentially read the content of a web page in audio. Unfortunately, screen readers are not able to detect the meaning of the different page objects, and thus the implicit semantic knowledge conveyed in the presentation of the page is lost. One approach described in literature to tackle this problem, is the Dante approach, which allows semant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(13 citation statements)
references
References 19 publications
0
7
0
6
Order By: Relevance
“…The main goal in Plessers et al [21] is to generate the annotations for visually impaired users automatically from the explicit conceptual knowledge existing during the design process. The approach integrates the Dante [31] annotation process into the Web Site Design Method (WSDM) [9] that allows Web applications to be developed in a systematic way.…”
Section: Related Work and Discussionmentioning
confidence: 99%
“…The main goal in Plessers et al [21] is to generate the annotations for visually impaired users automatically from the explicit conceptual knowledge existing during the design process. The approach integrates the Dante [31] annotation process into the Web Site Design Method (WSDM) [9] that allows Web applications to be developed in a systematic way.…”
Section: Related Work and Discussionmentioning
confidence: 99%
“…Some studies have been found that propose the application of WCAG to Semantic Web technologies such as ontologies, XML, XMLSchema and OWL [29,30]. Among the relevant studies found in the area of Web engineering methods, some propose the use of patterns on a method to include certain accessibility requirements in user interfaces [31] and others focus on a user-friendly approach that uses well-designed access patterns to provide efficient access in the navigation and retrieval of information for a website [32].…”
Section: Related Workmentioning
confidence: 99%
“…Thus, none of the previous approaches fully satisfy the accessibility standards. However, one interesting attempt meriting particular mention is the Dante approach, integrating the Web Authoring for Accessibility (WAfA) ontology [33,34] for the visually impaired into the WSDM method [30]. In this study, the Accessibility Web Applications (AWA) approach has been adopted.…”
Section: Related Workmentioning
confidence: 99%
“…In combination with the Web Site Design Method (WSDM) [1] it is possible to fully automate the generation of semantical annotations used for Dante [15]. It is approximated that 85% of the annotations can be provided that way.…”
Section: Related Workmentioning
confidence: 99%